"Blood Has No Colour": Racialized Donor In/Ex-clusion in the South African National Blood Service. Issue 3 (3rd April 2023) - Avera, Emily
ABSTRACT: Accounting for challenges with HIV transmission and testing, the South African National Blood Service (SANBS) transitioned toward eliminating race as a risk categorization in 2005 and actively recruiting black donors. I trace the racialization and nationalization of blood through an analysis of this transition, outreach efforts, and data from fieldwork with blood donors and SANBS staff. I examine indexicality as a semiotic means of in/ex-clusion in blood donation. Due to the sociocultural and medical significance of blood, an ethnographic account of blood services provides insights into biological citizenship and the dynamics of justice and reconciliation in post-apartheid South Africa.